Research on realistic remote exploration service - Kwihoon Kim; Woongshik You; Ohyung Kwon (2012 8th International Conference on Computing and Convergence Technology, 2012)
This paper is to provide implementation performing remote exploration through a remote explorer terminal based on a user terminal or a screen connected to the Internet. Particularly, this technology is for recommending a remote explorer to a user, and providing a user with the image or the video taken by the remote explorer terminal.